Relationship between body composition indicators and physical capacity of the combat sports athletes - Durkalec-Michalski, K.; Podgorski, T.; Sokolowski, M.; Jeszka, J. (Archives of Budo, 2016)
Background and Study Aim: In combat sports a modification of body weight should be based on an appropriate regulation of body composition, preferably after establishing the optimal level of tissue components. In view of the above the aim of this study was the relationship between body composition indicators and physical capacity of the combat sports athletes with prospect of most advantageous exercise-induced adaptation.